Key predictors of academic success in flexible learning environments: a PLS-SEM analysis - Manulat, Jessa B. (Frontiers in Education, 2025)
This study analyzed the predictors of academic success in flexible learning environments among the college students who experienced the flexible learning modality from a state university in Cebu, Philippines. Specifically, it examined how academic success is affected by the key predictors such as the school climate, motivation, personal development, and study habits. The study was conducted among the 1,113 purposively sampled second to fourth year students enrolled in various academic programs across the different satellite and extension campuses of the university. It employed a descriptive quantitative research design. The data were gathered using an online survey through Google Forms. Data gathered were then analyzed using Partial Least Squares Structural Equation Modeling (PLS SEM) to determine the relationships between the identified key predictors and academic success. Findings revealed that school climate, personal development, and study habits significantly predict academic success. However, motivation was not one of the significant predictors in the context of academic success in flexible learning environments. Based on the findings, it is concluded that both institutional and individual factors—such as ensuring a supportive and conducive school climate, improving students' personal development, and cultivating a structured study habits—are essential to achieving academic success in flexible learning environments. The study recommends the development and implementation of targeted intervention programs to address these factors and enhance students' success in similar education settings.